Магнитные жидкости: справочное пособие / В. Е. Фертман - Фертман Вячеслав Ефимович (Вышэйшая школа, 1988)
Экземпляры: КХ (20110729) / Инвентарный номер: 919642 / Цена: 0.85 / Сис.шифр: 22.253 / Авт.знак: Ф 43 / ГРНТИ: 30 / ББК: 22.253.345